1998
DOI: 10.1007/s004380050880
|View full text |Cite
|
Sign up to set email alerts
|

The gene cluster inlC2DE of Listeria monocytogenes contains additional new internalin genes and is important for virulence in mice

Abstract: In this work we identified and characterized a gene cluster containing three internalin genes of Listeria monocytogenes EGD. These genes, termed inlG, inlH and inlE, encode proteins of 490, 548 and 499 amino acids, respectively, which belong to the family of large, cell wall-bound internalins. The inlGHE gene cluster is flanked by two listerial house-keeping genes encoding proteins homologous to the 6-phospho-beta-glucosidase and the succinyl-diaminopimelate desuccinylase of E. coli. A similar internalin gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
107
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 39 publications
(41 reference statements)
6
107
1
Order By: Relevance
“…Functional implications. Several members of the LPXTG protein family have been shown to be involved in the virulence of L. monocytogenes (1,22,40). Of particular interest, internalin, which is required for entry into human Caco-2 cells in vitro, had as good as no effect on bacterial virulence in the mouse model, even upon administration by the oral route (14,22).…”
Section: Discussionmentioning
confidence: 99%
“…Functional implications. Several members of the LPXTG protein family have been shown to be involved in the virulence of L. monocytogenes (1,22,40). Of particular interest, internalin, which is required for entry into human Caco-2 cells in vitro, had as good as no effect on bacterial virulence in the mouse model, even upon administration by the oral route (14,22).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these confirmed virulence genes, three other internalins (inlC2, inlD, and inlE) also showed significant expression ratios of Ͼ2.0 under osmotic and/or stationary-phase stress (Table 2). PCR mapping showed that the L. monocytogenes strain used in our study (10403S) bears an inlC2DE operon rather than an inlGHE operon, which is present in the L. monocytogenes EGD-e strain (57). Each ORF of the inlC2DE gene cluster is potentially transcribed independently of the others (13).…”
Section: Hmmmentioning
confidence: 96%
“…Both of these internalins belong to a large listerial protein family which in L. monocytogenes includes at least seven more internalins (12,13,43), all of which are typical members of the leucine-rich repeat superfamily that includes many other eukaryotic and prokaryotic proteins (26,27). With the exception of InlC and InlB, the internalins have in their C-terminal portions a conserved region with an LPXTG motif, which anchors these proteins to the peptidoglycan of the bacterial cell surface (36).…”
mentioning
confidence: 99%
“…Besides InlA and InlB, only InlC, InlC2, InlD, InlE, InlF, InlG, and InlH have been studied so far to some extent (12,13,43). In contrast to InlA and InlB, none of these internalins seem to be able to induce phagocytosis by nonphagocytic mammalian cells (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation